The Development of Activity-Based Textbooks on Animalia-Invertebrate Materials for Senior High School 10th Grade Students - Rakmawati, Rakmawati; Ambarwati, Reni (Journal of Biology Education, 2020)
Activity-based books contain features that emphasize students’ activity, therefore suitable for Invertebrate learning, because have material characteristics that require practical activities. The purpose of this study was to produce activity-based textbooks on Animalia-Invertebrate material, which valid, practical, and easy to be used by senior high school 10th grade students. Meanwhile, the specific purposes of this research were to describe the validity of instructional textbook based on content, linguistic, and presentation validity; to describe the practicality of activity-based book based on the implementation of learning, book readability of textbooks using Fry chart; and to describe the student's response to the ease of use of activity-based textbooks on Animalia-Invertebrate materials by senior high school 10th grade students. This research was conducted from August 2017 until March 2018. This developmental research was referred to 4D model (define, design, develop, and disseminate), but disseminate stage was not done. The development of textbooks was conducted in the Biology department of UNESA and limited trials were conducted on 20 students of SMAN 12 Surabaya class of 10th MIA 2. Validation, practically based on implementation and readability, and student’s responses were analyzed descriptive-quantitatively. The results showed that the developed textbooks got a very decent category mode. The percentage of textbook implementation was 100% and the textbook readability was at the level of legibility of 10. In addition, the students gave positive responses, the average score was 99.74% (positive category). Hence, it can be concluded that the textbook was valid, practical, and easy to be used for Biology learning.